2003
DOI: 10.1113/jphysiol.2002.034173
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the human muscle nicotinic receptor, and of the slow-channel myasthenic syndrome mutant  L221F, inferred from maximum likelihood fits

Abstract: The mechanisms that underlie activation of nicotinic receptors are investigated using human recombinant receptors, both wild type and receptors that contain the slow channel myasthenic syndrome mutation, epsilonL221F. The method uses the program HJCFIT, which fits the rate constants in a specified mechanism directly to a sequence of observed open and shut times by maximising the likelihood of the sequence with exact correction for missed events. A mechanism with two different binding sites was used. The rate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 56 publications
9
114
0
Order By: Relevance
“…We therefore proceeded to test whether adding extra shut states to the unconstrained form of scheme 1 helped account for observed channel behavior. Only a slight improvement was detected when a single shut state was added in a position distal to either A 3 R or A 3 R* (Salamone et al, 1999;Hatton et al, 2003) (data not shown). Adding a distal shut state to scheme 1 or scheme 2 (while keeping the constraint of binding site independence) also failed to produce any detectable improvements in the quality of the fit.…”
Section: Additional Bound Shut Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore proceeded to test whether adding extra shut states to the unconstrained form of scheme 1 helped account for observed channel behavior. Only a slight improvement was detected when a single shut state was added in a position distal to either A 3 R or A 3 R* (Salamone et al, 1999;Hatton et al, 2003) (data not shown). Adding a distal shut state to scheme 1 or scheme 2 (while keeping the constraint of binding site independence) also failed to produce any detectable improvements in the quality of the fit.…”
Section: Additional Bound Shut Statesmentioning
confidence: 99%
“…Simulation of repeated fits showed that our data, with the HJCFIT algorithm, are capable of making good estimates of all 14 free rate constants in the flip mechanism, including the opening rate of the fully liganded receptor, ␤ 3 , which, at approximately 130,000 s Ϫ1 , is approximately twice as fast as for a nicotinic receptor (Salamone et al, 1999;Hatton et al, 2003).…”
Section: Mechanism Versus Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few lines of experimental evidence showing the contribution of M1 to channel gating (Lo et al 1991, Engel et al 1996, Croxen et al 2002, Hatton et al 2003. Our study identifies position 15?…”
Section: Discussionmentioning
confidence: 57%
“…A mutation in oM1 has been also shown to be the cause of a congenital myasthenic syndrome mainly due to an increased affinity of ACh for the resting AChR (Croxen et al . 2002, Hatton et al . 2003.…”
Section: Introductionmentioning
confidence: 95%